Percentage of consumption of herbal medicines during and after the pandemic between 2020 and 2023 in a school pharmacy in Teresina City, Piauí (PI) State, Brazil (Research, Society and Development, 2024)
This study examined the impact of the COVID-19 pandemic on the consumption of herbal medicines in the teaching pharmacy of a university center in Teresina/PI, between 2020 and 2023. With social isolation directly interfering with people's emotional and immunological health, the study sought to understand how the pandemic influenced the demand for these medicines. The objective was to evaluate the percentage of consumption of herbal medicines before, during, and after the pandemic. The methodology included a cross-sectional, retrospective, qualitative, and quantitative approach, with data collected manually in May 2024, considering the monthly and annual consumption of herbal medicines. The results show that in 2020, at the height of the pandemic, there was an increase in the number of herbal medicines sold as the months went by. In 2021 and 2022, this downward trend was consolidated, with an average 50% reduction in consumption. However, in 2023, after the pandemic, consumption grew again, registering a significant increase of 70%. The study provides valuable insights into the consumption behavior of herbal medicines in the context of the pandemic and post-pandemic, contributing to future research and offering important subsidies for health professionals and academics, particularly in the use of herbal medicines in times of health crises.